2004
DOI: 10.1007/s10147-004-0395-3
|View full text |Cite
|
Sign up to set email alerts
|

Local hyperthermia combined with external irradiation for regional recurrent breast carcinoma

Abstract: The present findings suggested a significant benefit of local hyperthermia combined with radiotherapy in the treatment of locally recurrent breast cancer, especially for previously irradiated recurrence, by reducing the total irradiation dose. Diffuse/multiple small nodular tumors respond earlier than bulky/large nodular tumors; however, they tend to recur within the treatment field. The purpose of this study was to evaluate the therapeutic effects of hyperthermia in combination with radiotherapy for locoregio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 11 publications
2
25
0
Order By: Relevance
“…In 1996 the International Collaborative Hyperthermia Group (ICHG) published the results of a combination of five phase III trials, demonstrating the efficacy of hyperthermia as an adjunct to radiotherapy for the treatment of recurrent breast cancer. These results were confirmed by more recent studies [11][12][13].…”
Section: Introductionsupporting
confidence: 94%
“…In 1996 the International Collaborative Hyperthermia Group (ICHG) published the results of a combination of five phase III trials, demonstrating the efficacy of hyperthermia as an adjunct to radiotherapy for the treatment of recurrent breast cancer. These results were confirmed by more recent studies [11][12][13].…”
Section: Introductionsupporting
confidence: 94%
“…Locoregional recurrences of breast cancer may be the cause of severe suffering when uncontrolled, with symptoms such as pain, ulceration, and bleeding. Systemic treatment usually is less effective in a region previously irradiated [13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The large penetration depth of capacitive systems would in principle be very beneficial to heat these tumours at full depth, where standard radiative superficial hyperthermia equipment operating at high frequencies (434-2450 MHz) has an insufficient penetration of the electromagnetic energy. Clinical studies report feasibility of heating bulky tumours with capacitive systems and reported tumour temperatures are in the therapeutic range (40)(41)(42)(43)(44) C) [8,12,33,34]. However, clinically measured temperatures using a limited number of thermometry probes do not provide full information about the 3D temperature distribution and Van Rhoon et al reported the need for extensive thermometry to avoid missing hot spots that could lead to subcutaneous burns [32].…”
Section: Discussionmentioning
confidence: 99%